I dig dirt [videorecording (DVD)] (Dreams Come True Productions ; Distributed by Big Kids Productions, 2000)
See super earth-moving equipment in action and up close. Marvel at the biggest dump truck in the world that moves 240 tons of dirt in one load, and other giant machines.